Peeling Easter Eggs: How to lie like an Oulipian - DeCoster, Esmé Clare (Trinity College Dublin, SLLCS, 2026)
Taking up as its sources three long-form novels written by Oulipian members of the second cohort: La Disparition by Georges Perec, Se una notte d’inverno un viaggiatore by Italo Calvino and The Sinking of Odradek Stadium by Harry Mathews, this dissertation argues that there are common techniques of literary untruth which are used in each and which form a Oulipian technique of lying. By collecting these untruths under the categories: wholly untrue, truth paired untrue, truth rewritten, untruth characterized, along with narrative exhortation to paranoia and repetition of terms, this dissertation uses a comparative approach to put forth a concept of the Oulipian project to disorient the readers of their constrained texts. By categorizing and showing the spectrum of deceit amongst these texts, all written within a short span of years and by authors who share an affiliation (Oulipo), one can extrapolate a possible paranoid reader response and consider the appeal these texts have to readers of the 21st century.